2011
DOI: 10.1002/app.34295
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic, magnetic, and optical characterization of nanocomposite films of polyvinylpyrrolidone doped with cerium disulphate

Abstract: New nanocomposite hybrid films of a well dispersed cerium disulphate Ce(SO 4 ) 2 nanoparticles into the polyvinylpyrrolidone (PVP) matrix were prepared by a casting technique. The nanostructural nature and complex formation were investigated using the transmission electron microscopy (TEM), the nuclear magnetic resonance (NMR), and the Infrared (IR) spectroscopy. The magnetic measurements at room temperature, using a vibrating sample magnetometer (VSM), and the obtained magnetic parameters revealed that the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…To understand the controlled hydrolysis of Ti alkoxides and their subsequent transformation in the prepared sol–gel solutions, FTIR method has showed promising results . Thus, the “one‐pot” sol solutions of TIP/AcOH in 2‐propanol with PVP (3 wt %) and without it and the electrospun TiO 2 /PVP nanofibers were studied by FTIR spectroscopy technique (after their preparation at room temperature) as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the controlled hydrolysis of Ti alkoxides and their subsequent transformation in the prepared sol–gel solutions, FTIR method has showed promising results . Thus, the “one‐pot” sol solutions of TIP/AcOH in 2‐propanol with PVP (3 wt %) and without it and the electrospun TiO 2 /PVP nanofibers were studied by FTIR spectroscopy technique (after their preparation at room temperature) as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it can be used in non‐aqueous solutions, as well. This polymer has showed extensive applications in the synthesis of nanostructures, since carbonyl group in pyrrolidone ring can make complex with many inorganic species …”
Section: Resultsmentioning
confidence: 99%
“…As can be seen in the inset of Figure 5, Ce(SO 4 ) 2 presents characteristic peaks at 225 nm, 240 nm, and 320 nm, values that are close to those reported in the literature. In addition, Basha and coworkers found a peak at 290 nm attributed to electronic transition 5d→4f [18]. Ce(SO 4 ) 2 addition changes the optical absorbance at the UV region of PVDF, appearing as two "shoulders" close to 240 nm and 300 nm.…”
Section: Absorption Spectra (Uv-vis)mentioning
confidence: 99%
“…Role of PVP contributed to synthesis nanoparticles are surface stabilizers, shape control, reducing agents and dispersants [8]. However, study composite films PVP with nano particles was found on optical improvement using Ce(SO4)2 [9] and Ag and Au [10].…”
Section: Introductionmentioning
confidence: 98%